Central Bank Forecasts of Policy Interest Rates: An Evaluation of the First Years. (February 2014) - Beechey, Meredith; Österholm, Pär
<x xml:space="preserve">Abstract</x> In recent years, the central banks of Norway and Sweden have published their endogenous policy interest‐rate forecasts. In this paper, we evaluate those forecasts alongside policy‐rate expectations inferred from market pricing. We find that for both economies, there are only small differences in relative forecasting precision between the central bank and market‐implied measures. However, both types of forecast fail tests for unbiasedness and efficiency at longer horizons.